Analisis Pelaksanaan Lelang Online (E-Auction) di Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Kota Medan - Saparuddin Siregar; Sylviana Siregar (Khidmatussifa: Journal of Islamic Studies, 2023)
Online Auction (E-Auction) is an auction that is carried out without meeting face-to-face and can be carried out remotely through the Indonesian auction website and application. The online auction process can be carried out easily and efficiently, starting from transparent information processes to bidders, bidding, transactions and payments. This type of research uses quantitative methods with a case study research approach with a predetermined research time. The results of the research show that the implementation of online auctions has advantages to be developed and implemented. However, not many people know about and participate in online auctions because socialization has not spread widely. Keywords: Auction Implementation, Online Auction, State Asset Service Office andAuction.